Emergency Peripartum Hysterectomy: A Life Saving Procedure in Obstetrics (Faridpur Medical College Journal, 2018)
Emergency peripartum hysterectomy refers to the uterine removal after a caesarean section or normal vaginal delivery for any life saving purpose, immediately after delivery or within the puerperium. In general, abnormal placentation, uterine rupture, and postpartum haemorrhage are the common indications. The prime objective of this study was to determine the frequent indications, peroperative and postoperative complications, maternal and perinatal outcome. This retrospective descriptive study was conducted by analysing recorded data of one year between July 2016 and June 2017 in Faridpur district of Bangladesh. Total 40 cases were analysed. Placenta praevia was the most common indication, whereas uterine rupture was the second one. Urinary bladder injury was the frequent peroperative complication. This bladder injury was common in cases of previous repeated caesarean section associated with placenta praevia. All the patients required three to six unit blood transfusions on average. Four patients expired due to various causes. Most of the patients were elderly aged, multiparous and had previous caesarean sections. The relevant literature analysis was done for comparison, where similarities were found. Total abdominal hysterectomy was the preferred method in this study. Overall, the study will direct the future ways of management.Faridpur Med. Coll. J. Jan 2018;13(1): 12-16